EXECUTIVE COMMITTEE WORKING GROUP: WOMEN IN ASTRONOMY - Primas, Francesca; Maddison, Sarah; Aerts, Conny; Clayton, Geoffrey; Combes, Françoise; Elmegreen, Debra; Feretti, Luigina; Jog, Chanda; Kobayashi, Chiaki; Lazzaro, Daniela; Liang, Yanchun; Mandrini, Cristina; et al. (Proceedings of the International Astronomical Union, 2015)
The gender† dimension of science and technology has become one of the most important and debated issues worldwide, impacting society at every level. A variety of international initiatives on the subject have been undertaken, including the continued monitoring of the status of women in science by Unesco Institute for Statistics (UIS) or the annual reports “Education at a Glance” by the Organization for Economic Co-operation and Development (OECD) as well as field-related working groups and networking in order to collect data in a consistent manner. The majority of the international organizations have made clear statements about their discrimination policies (independently of their main field(s) of action), including the International Council for Science whose regulations are followed by the IAU. Gender equality at large is one of the eight United Nations Millennium Development Goals, which clearly calls for action related to science, technology and gender.